Challenges to the Use of a Base of Fresh Water in Groundwater Management: Total Dissolved Solids vs. Depth Across California - Warrack, Jessica; Kang, Mary (Frontiers in Water, 2021)
According to the California Sustainable Groundwater Management Act, the bottom of a basin, and subsequently the depth to which groundwater is managed, can be defined through physical or geochemical qualities of the aquifer. Total dissolved solids (TDS) concentrations are most frequently used to define the basin bottom. However, upper limits in TDS concentrations for “fresh” and “useable” groundwater can range from 1,000 mg/L to 10,000 mg/L. To evaluate the applicability of using TDS concentrations to delineate depths subject to sustainable groundwater management, we analyze 216,754 TDS measurements throughout the state of California. We find major challenges to reasonably estimating the BFW with our dataset in 73% of California due to data insufficiencies or complexity introduced by nonmontonic TDS-depth relationships. We estimate the BFW in 22% of the Central Valley, a key agricultural region with large groundwater demands and many critically overdrafted groundwater subbasins. Using a TDS limit of 3,000 mg/L, where possible, we estimate the shallowest BFW in the Central Valley to be 155 m below ground surface and the deepest BFW to be 589 m below ground surface. We find that the base of brackish water (TDS<10,000 mg/L) can extend more than 500 m deeper than the BFW in 78% of the Central Valley where we are able to estimate the BFW, which corresponds to 2% of California. There is a need to evaluate alternative strategies for defining groundwater subject to sustainable management, which likely involves additional measurements and analysis to better characterize groundwater quality with depth throughout California.